A step back to look ahead: Mapping coalitions on data flows and platform regulation in the Council of the EU (2016-2019) - Clément Perarnaud (Internet Policy Review, 2021)
As new legislative battles arise on the EU digital policy front, this article draws on recent EU negotiations related to the making of the Digital Single Market (DSM) to document the main lines of division between member states in this field, as well as coalition patterns in the Council of the EU. This research draws on a novel data set on the policy preferences and salience of member states in key controversial negotiations related to the regulation of data flows and internet platforms. It provides relevant analytical tools to approach future EU digital policy-making processes by investigating recent coalition patterns in the Council and beyond.
Keywords: 300; Council of the EU; Coalitions; Digital Single Market; Data flows; Internetplatforms; Digital platforms